PRAKTIKALITAS E-LKPD BERBASIS STEM-PjBL DALAM PEMBELAJARAN IPA FASE B - Diana Rossa Martatiyana; Hadi Nasbey; Nidya Chandra Muji Utami (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
The presentation of LKPD, especially in science learning, needs to experience innovation, including the use of technology to improve the quality of learning, namely by developing E-LKPD. Previous research has developed a STEM-PjBL based Science E-LKPD, but the response of class IV students to the E-LKPD is not yet known. This research aims to determine students' responses to STEM-PjBL-based Science E-LKPD. This research uses qualitative data and quantitative data. The research results were obtained based on the results of the student and teacher response instruments to the STEM-PjBL based Science E-LKPD which got an average percentage of 83% on the one to one test UI and the students' response results got an average percentage of 95% with very good category in small group trials, and teacher responses were 93%, all of which reflect suitability and excellence in various important aspects of learning.